Flexural and shear behaviour of lightweight expanded polystyrene precast concrete half-slab - Saheed, Sanusi (2014)
Industrial Building System (IBS) design is a building system in which structural components are manufactured in a factory, or off site, transported, and coupled into a structure with less additional site works (CIDB, 2001). However, the main problems with precast components are its heavy weight and water leakage at the joint between the precast slabs. Hence, this research aims at producing a lightweight precast slab that could overcome the second problem as well. Lightweight aggregate concrete is made from three main resources, namely natural aggregates (pumice, scoria, vermiculite, etc.), manufactured aggregates (e.g. Expended clay, expanded silt, Expanded polystyrene (EPS) etc.) and aggregates from industrial by-products (Delayed et al 2006). These lightweight aggregates have many advantages among which are low densities, reduced thermal conductivity, easy handling and high energy absorption. However, the easiest to purchase and practical to use is the EPS beads. EPS beads in concrete have shown sufficient early age strength but reduced the strength of concrete at 28 days. Hence, to address this,Ilangovana (2008) have recommended quarry dust as replacement to fine aggregate by about 20% to improve the compressive strength of EPS concrete. Based on these previous works, the first objective of this research is to determine the optimum mix design of lightweight concrete using quarry dust and Expanded Polystyrene (EPS) based on the targeted compressive strength of 35 MPa, which is sufficient for structural application. An experimental study was conducted to develop the lightweight concrete by partial replacement of sand and coarse aggregates using quarry dust and Expanded Polystyrene (EPS). Sand replacements used were 7.5%,15% and 22.5%, while coarse aggregate was replaced by EPS beads at 15%, 22.5% and 30% by volume of the mix. A total of 256 trial mixes were made and their mechanical behaviour in terms of compressive strength test, split tensile strength test, Ultra Pulse Velocity test (UPV) and unit weight test were measured, from which the optimum mixture for grade 35 concrete was chosen and used to produce lightweight EPS slabs. There are numerous types of precast slab includes hollow core, half slab, double tee and metal deck. However, to prevent leakage between the slabs and improve connectivity between panels, Ng et al (2011) suggested a C-channel half slab because apart from mentioned advantages, it also does not require propping and therefore less formwork is needed. Therefore, using the optimum lightweight EPS concrete, precast C-channel half slabs were produced and subjected to flexural and shear tests as these two behaviours are the dominant contribution during the lifespan of the slab. Normal weight concrete slabs were also produced as control specimens. In total, 10 precast concrete C-channel half slabs of 1 m width by 3.5 m, 4.5 m and 6.0 m span were prepared. Five slabs were made of normal weight concrete and another five of lightweight EPS concrete. On the other hand, 4 numbers of precast slabs both lightweight and normal weight concrete of 200 mm and 250mm thickness were produced and subjected to direct shear load test at span of two times the depth of the slab. During the tests, the ultimate load, deflection behaviour,ductility, reinforcement strain, shear capacity and failure patterns were observed and analysed. Based on the compressive strength of a few trial mixes, the optimum mix of lightweight EPS concrete of compressive strength 35 MPa was achieved by the replacement of 30% EPS and 15% quarry dust in the concrete. This produces lightweight concrete with a density of 1980 kg/m3, which is 17% lighter than normal concrete. This lighter concrete will significantly reduce the total self-weight of the structures and subsequently will reduce the size of foundation required and reduce the overall cost of the structure. The flexural and shear of EPS lightweight half slab showed a comparative capacity as compared to normal weight slab. The ultimate bending moment capacity for lightweight precast C-channel slabs has approximately the same capacity as normal weight precast C-channel for a slab span of 3.5 m, 4.5 m and 6 m respectively. These show that reduction in the dead load due to the EPS lightweight concrete matrix has not reduced its ability in carrying loads regardless of the span of the slab. In terms of the ductility, precast lightweight C-channel slab achieved ductility ratio of 2.9 - 3.1 higher than the normal concrete of 2.2 -2.6. This explained why the lightweight precast channel slabs give more cracks signs before failure and this will provide a safer structure to the user. On the other hand, the ultimate shear capacity for lightweight precast C-channel slabs with lightweight concrete topping with 200 mm and 250 mm depths show a reduction of shear capacity by 6 % and 12% respectively as compared to the experimental capacity of normal concrete C-channel precast slab. However, when compared to the theoretical calculation, experimental shear capacity of lightweight precast C-channel slab for 200 mm and 250 mm depths is 26% and 32% higher than the calculated value. This shows that the shear capacity of lightweight precast slab is sufficient and can be predicted by the theoretical shear calculation for normal concrete. Inclusion, it can be stated that the precast EPS lightweight precast C-channel half slab can be estimated using a similar theoretical calculation for normal concrete. Also, as the self-weight of the slab is reduced, the foundation size can be reduced too, which directly will also contribute in a cost saving of the whole structure. Therefore the lightweight precast C-channels half slab could be used as a flooring system in single and double story housing construction.